2021
DOI: 10.1371/journal.pone.0250231
|View full text |Cite
|
Sign up to set email alerts
|

Changing parental feeding practices through web-based interventions: A systematic review and meta-analysis

Abstract: Web-based parent interventions designed to promote children’s healthy eating patterns can enhance parents’ engagement and facilitate behavior change. However, it is still unclear how much the existing programs focus on changing parental feeding practices, and if so, which behavioral methodologies are used and how effective these interventions are in changing these parental behaviors. This systematic review and meta-analysis studied randomized controlled trials of web-based interventions targeting parents of 0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 68 publications
(157 reference statements)
0
39
0
Order By: Relevance
“…In some programs, parents not always defined objective, reachable, and realistic goals [ 28 ], which might compromise the intervention’s efficacy. We systematically reviewed several parental online interventions to promote children’s healthy eating and positive feeding practices and found that parents rarely received feedback about monitoring their behaviors or information about accomplishing the goal set [ 8 ]. In our program, a list of goals based on the parents’ needs identified in the baseline guided parents in choosing the feeding behaviors to improve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some programs, parents not always defined objective, reachable, and realistic goals [ 28 ], which might compromise the intervention’s efficacy. We systematically reviewed several parental online interventions to promote children’s healthy eating and positive feeding practices and found that parents rarely received feedback about monitoring their behaviors or information about accomplishing the goal set [ 8 ]. In our program, a list of goals based on the parents’ needs identified in the baseline guided parents in choosing the feeding behaviors to improve.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was clearly described regarding the components and contents of the intervention, detailing the parental feeding practices and children’s dietary outcomes targeted by the intervention and providing a categorization of the BCTs used in both arms. The power size and the sample size estimation were based on systematic reviews carried out with similar studies [ 8 , 32 , 33 ]. For this calculation, we adopt a more conservative approach to determine the dropout rate, to accommodate some issues found in online parental interventions and further limitations due to the current coronavirus disease (COVID-19) pandemic context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review 38 of web-based interventions to change parent feeding practices for children up to 12 years of age identified seven studies that included children younger than 5 years, one targeting parents of infants, and the remainder focused on preschool children. Some of these studies had a broader focus (eg, obesity prevention) and hence also included one or more movement behaviours in their intervention.…”
Section: Introductionmentioning
confidence: 99%